The English as a Foreign Language Learners’ Psychological and Emotional Perceptions on Technology Integration in Language Classrooms - Yu, Xiao (Frontiers in Psychology, 2022)
Recently, the use of new educational technologies in language teaching development is expanding rapidly. Educational technologies attach new features to the learning environments. The integration of educational technologies in language teaching has been received special attention among language researchers. In so doing, the present study investigated language learners’ perceptions of the integration of innovative educational technologies in their language classrooms. The sample comprised 301 English as a foreign language (EFL) students with different academic qualifications from Shaanxi Province (299) and other provinces (Fujian province=1, Sichuan province=1) in China. To gather the necessary data, the researcher conducted a technology integration questionnaire and a focus group interview. The results of obtained data demonstrated that the language learners had positive attitudes towards using technology in their classrooms. However, the findings of the interviews indicated that learners had some problems such as lack of technology literacy and inadequate assess to facilities in participating in technology-based classroom activities.